ROLE OF BACTERIAL SIDEROPHORES IN DISSOLUTION OF HORNBLENDE - Liermann L.J.; Kalinowski B.E.; Brantley S.L.; Ferry J.G. (My University, 2000)
Hornblende, a common mineral in granitic soils, may act as a source for a variety of metals needed by bacterial species for enzyme function (e.g., Fe, Zn, Mn, Cu, Co, Mo, V, Ni). A species of the bacterial genus Streptomyces was cultured from an Adirondack soil and isolated because of its ability to grow robustly in low Fe medium with hornblende present. Studies with unbuffered culture medium, to discover whether Streptomyces sp. cultures affected solution pH, showed a decrease of 2.0 pH units in 21 d, then an increase of 3.0 pH units at 56 d. Cells that adhered to the hornblende surface at 56 days were difficult to remove, presumably because of mycelial growth deep into pits and cracks. Decreases and increases in pH may have been due to production of organic acids and ammonia respectively. Increases in pH could also have been related to release of components during death of organisms. In a buffered medium, Streptomyces sp. increased the initial Fe release rate from hornblende approximately fivefold over that of an abiotic control. A catechol derivative, produced by the Streptomyces sp. and characterized by chromatography and mass spectrometry, is presumed to cause this Fe release enhancement. Hornblende dissolution was also analyzed in the presence of a commercially available hydroxamate siderophore, desferrioxamine mesylate (DFAM). DFAM is the methane sulfonate form of one of many siderophores known to be a product of streptomycetes. The rate of Fe release obtained when incubating the hornblende with 24 μm of DFAM was similar to the rate observed in the presence of the Streptomyces sp. isolate. Higher concentrations of DFAM increased the dissolution rate nonlinearly, described by the rate equation R = (7.6 x 10-13)C0.47, where R is the release rate of Fe (mol/m2s), and C is the concentration (mol/l) of DFAM. The DFAM also increased release of Al and Si from hornblende into solution; however, these release rates were not increased by addition of the Streptomyces sp. alone. Preferential release of Al and Si in the presence of DFAM, but not in the presence of bacteria alone, may be related to the difference in selectivity of catechol vs. hydroxamate siderophores. Addition of Streptomyces sp. in the presence of DFAM at three concentrations consistently enhanced Fe release approximately two to threefold the rate with siderophore alone. Recycling of siderophore molecules or enhanced production of one siderophore by microorganisms in the presence of other siderophores makes it difficult to predict a priori release rates when both siderophore and bacteria are present, as would be the case in natural soils.